Catalyzed Hairpin Assembly-Assisted DNA Dendrimer Enhanced Fluorescence Anisotropy for MicroRNA Detection - Tianjin Xie; Yuxin Liu; Jiali Xie; Yujie Luo; Kai Mao; Chengzhi Huang; Yuanfang Li; Shujun Zhen (Chemosensors, 2022)
Biomacromolecules have been employed successfully as fluorescence anisotropy (FA) amplifiers for biosensing in reported studies. However, the sensitivities of the traditional biomacromolecule amplified FA strategies need to be improved because of the relatively low molecular weight or volume of a single biomacromolecule and the 1:1 binding ratio between the fluorophore-linked probe and target. In this work, a DNA dendrimer with a high molecular weight and volume was employed as a new FA amplifier, which was coupled with target-catalyzed hairpin assembly (CHA) for the sensitive detection of miRNA-21. The fluorophore-modified probe DNA (pDNA) was fixed on the DNA dendrimer, resulting in a high FA value. The addition of miRNA-21 triggered the CHA process and produced plenty of H1-H2 hybrids. The complex of H1-H2 bound to the DNA dendrimer and released the pDNA through a toehold-mediated strand exchange reaction. Thus, a low FA value was obtained because of the low mass and volume of free pDNA. Based on the dramatically reduced FA, miRNA-21 was detected in the range of 1.0–19.0 nM and the limit of detection was 52.0 pM. In addition, our method has been successfully utilized for miRNA-21 detection in human serum. This strategy is sensitive and selective and is expected to be used to detect other biomolecules simply by changing the corresponding nucleic acid probe.